Managerial Effectiveness Strategy of Education Foundations in Improving the Quality of Private Education - Ruswandi, Iwan; Bibin Rubini; Widodo Sunaryo (The Future of Education Journal, 2025)
This study aims to analyze the managerial effectiveness of foundation leaders in improving the quality of private educational institutions in Bogor, Indonesia. Conducting a quantitative approach, data were collected from 103 educational foundations through structured questionnaires directed at foundation leaders, supervisors, and principals. The analysis applied path analysis to examine the direct and indirect effects of four main variables: organizational culture, servant leadership, personality, and organizational commitment. Results revealed that servant leadership had the strongest direct influence on managerial effectiveness (β = 0.374), followed by organizational culture (β = 0.234), organizational commitment (β = 0.185), and personality (β = 0.157). While all independent variables also significantly influenced organizational commitment, their indirect effects on managerial effectiveness through commitment were found to be weaker. Thus, organizational commitment was not an effective mediating variable. The study proposes an empirical model for enhancing managerial performance and offers strategic recommendations for foundation leadership development and educational governance improvement.